An annotated checklist of crickets, grasshoppers and their allies (Orthoptera) in Slovakia - Krištín, Anton; Jarčuška, Benjamín; Kaňuch, Peter (Zootaxa, 2020)
The first annotated checklist of ensiferan and caeliferan Orthoptera of Slovakia is presented. Altogether, we found 129 species (59 Ensifera, 70 Caelifera) in the fauna of Slovakia, based on a critical revision of museum collections, all records published since 1826 and our own unpublished data from mapping in 1994–2019 ( 2000 sites located in 97.5% of the mapping grid cells). Forty-four species reach the limit of their distributional range within the country, and 31 have their northern limit there. Four species are endemic to Slovakia. In total, 11 species were erroneously reported from the country and are not included in this checklist. The relatively rich species spectrum reflects the diversity of habitats in an area of about 50 thousand km2 and elevations from 94 to 2,655 masl. We found 30 species exclusive for the Pannonian and 18 for the Alpine biogeographical region in the study area. We emphasize changes compared to previous species lists published in 1977 and 1999, when nine species were first recorded after 1999, and eight other species have been missing for more than 50 years. Distributional patterns, accompanied by site maps, are commented for 42 species. Taxonomic, nomenclatural and zoogeographical problems are discussed for a further 23 species. Based on the actual IUCN Red List criteria, we assessed all 129 species. The species were red-listed as follows: regional extinct (Celes variabilis), critically endangered (Isophya beybienkoi, I. costata, Poecilimon fussii, Pachytrachis gracilis, Saga pedo, Paracaloptenus caloptenoides, Acrotylus insubricus, Stenobothrus fischeri), endangered (Poecilimon intermedius, Gampsocleis glabra, Pholidoptera frivaldszkyi, Myrmeleotettix antennatus), vulnerable (nine species), near threatened (18) and data deficient (12). A brief account of the Orthoptera research history in Slovakia is outlined.